Interview with Prof. Frederic Chaume - Koverienė, Indrė; Višinskaitė, Indrė; Baltrūnaitė, Edita (Respectus Philologicus, 2020)
On the 19th of September 2019 Vilnius University, Kaunas Faculty welcomed a world-class researcher, Professor of audiovisual translation at Universitat Jaume I (Spain) and Honorary Professor at University College London (UK) Frederic Chaume. During a five-day visit, he presented a series of lectures and workshops titled Multimodal Research in Audiovisual Translation: Translation Paradigm of AVT Products in 2019.